Clinical adoption patterns of 0.35 Tesla MR-guided radiation therapy in Europe and Asia - Slotman, Berend J; Clark, Mary Ann; Özyar, Enis; Kim, Myungsoo; Itami, Jun; Tallet, Agnès; Debus, Jürgen; Pfeffer, Raphael; Gentile, PierCarlo; Hama, Yukihiro; Andratschke, Nicolaus; Riou, Olivier; et al. (Radiation oncology, 2022)
Magnetic resonance-guided radiotherapy (MRgRT) utilization is rapidly expanding, driven by advanced capabilities including better soft tissue imaging, continuous intrafraction target visualization, automatic triggered beam delivery, and the availability of on-table adaptive replanning. Our objective was to describe patterns of 0.35 Tesla (T)-MRgRT utilization in Europe and Asia among early adopters of this novel technology.